SNR Estimation Arithmetic Base on 1 Bit Quantization Correlator - Li Yuanling; Qu Xilong (IEEE Access)
A method for estimating the signal-to-noise ratio (SNR) using 1-bit quantization of the correlation value is proposed for the full-digital implementation of a spread spectrum receiver. Theoretical analysis, numerical simulation, and experimental verification results demonstrate that this method can achieve high-precision SNR estimation with minimal additional computational overhead.